Penyalahgunaan Jiwa Korsa sebagai Pemicu Tindak Pidana di Kalangan Prajurit: Studi Kasus Penyerangan Polsek Ciracas - Talitha Marshanda; Hery Firmansyah (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2024)
The misuse of the concept of esprit de corps among TNI soldiers can be a significant factor in the emergence of criminal acts, as seen in the case of the attack on the Ciracas Police in 2020. Esprit de corps, which reflects the spirit of collectivity and loyalty between members, often encourages soldiers to prioritize group solidarity over compliance with the law. There is a social theory in individual behavior that is influenced by group norms, in the context of strong solidarity criminal acts such as violence or retaliation become more likely to occur. In addition, social pressure and expectations of the military environment also strengthen this tendency. This article highlights several causal factors, including social injustice and the influence of military culture that contribute to negative behavior in certain situations to preventive efforts that can be taken to address the misuse of esprit de corps.